Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan Dan Efektivitas Samsat Keliling Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kabupaten Karangasem - I Komang Pasek Sandiasa; Ni Wayan Yuniasih; Rai Dwi Andayani W (UNHI Press, 2026)
Taxpayer compliance is recognized as the pivotal factor in achieving optimal regional tax collection, particularly for the Motor Vehicle Tax (PKB), which represents a substantial and crucial financial resource for local governments. Subsequent data analysis involved multiple linear regression, supported by standard statistical procedures including validity testing, reliability verification, and assessment of classical assumptions, alongside partial t-tests to validate the formulated hypotheses. The empirical results: (1) Taxpayer awareness significantly increases compliance; (2) Service quality likewise significantly strengthens compliance; and (3) The effectiveness of Mobile Samsat provides a significant improvement in taxpayer adherence. Consequently, the research recommends a strong policy emphasis on enhancing taxpayer awareness, systematically improving service quality, and guaranteeing the sustainable progress of the Mobile Vehicle Tax Office as essential strategies for long-term improvement in taxpayer compliance.